Improving efficiency and accountability: a case study on outsourcing strategies in higher education in Sri Lanka. (14th July 2010) - Herath, Siriyama Kanthi; Wickramasinghe, Danture; Indrani, M.W.
Less developed countries (LDCs) have given increasing emphasis to reduce the role of the government and to reform public sector management by adopting business-like management practices. Public sector reforms in Sri Lanka have been an interesting strategic initiative in the attempt to achieve enhanced efficiency, effectiveness and accountability. Privatisation is one major form of such reforms. This research reports the findings of a case study on outsourcing at a university. Motivations for outsourcing include cost reductions and budgetary constraints, expected improvement in service quality, lack of skilled staff and government regulations. Some limitations of outsourcing are lack of mutual understanding between the user and contractor, lack of awareness of users on the level of service, monopoly of the service, increased costs and reduced employee motivation. The research concludes that through careful management and partnership with outsourcing companies, universities can achieve improved levels of service and cost savings from outsourcing.